Dampak Jaminan terhadap Peluang Memperoleh Kredit bagi UMKM di Sumatera Barat - Marta, Joan; Satria, Doni (UI Scholars Hub, 2015)
This paper reveals that West Sumatera banking sector are more likely using the availability of collateral for the credit to micro, small and medium enterprises (MSME). Using 384 sample size from MSME in West Sumatera, if a MSME have enough collateral, the probability of their credit application to be rejected by banks will fall from 59.9% to 11.7% comparing to they don’t have enough collateral. This finding proved a credit guarantee scheme is needed, and for the further study it is recommended to conduct research on the characteristic of the potentials of MSME as a credit scoring model for banks.